Improving Students’ Learning Outcomes in Pancasila Education through Problem-Based Learning: A Classroom Action Research in Grade IV of SDN 011 Bukit Pedusunan - Maharani, Desti; Desyandri, Desyandri (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to improve students’ learning outcomes in Pancasila Education through the implementation of the Problem Based Learning (PBL) model, which is aligned with the principles of the Merdeka Curriculum in classroom instruction. Methodology: This study employed a Classroom Action Research (CAR) method conducted in two cycles, consisting of the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 18 students. Data collection techniques included learning outcome tests, observation sheets (non-test), and documentation of the instructional implementation as well as the quality of the teaching modules. Main Findings: The results of the study showed that prior to the intervention, only 11.1% of students achieved learning mastery. After the implementation of PBL, the quality of the teaching modules improved from 89.55% to 100%, the implementation of instruction increased from 91% to 96.4%, and the average student learning outcomes rose from 81.2 in Cycle I to 91.3 in Cycle II. Novelty/Originality of this study: This study presents the implementation of the Problem Based Learning model through Classroom Action Research in Pancasila Education within the Merdeka Curriculum. The novelty of this research lies in the integrated improvement of teaching module quality, instructional implementation, and learning outcomes simultaneously within the context of value-based Pancasila learning.